2014
DOI: 10.1097/tp.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti-Human Leukocyte Antigen and Anti-Angiotensin II Type 1 Receptor Antibodies With Liver Allograft Fibrosis After Immunosuppression Withdrawal

Abstract: Anti-AT1R Ab and DSA-DRB1 may be candidates as biomarkers of graft fibrosis; both HLA and non-HLA immunity may be involved in graft fibrosis after IS withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 39 publications
4
60
1
Order By: Relevance
“…Potential pathways of injury might not be easily linked to DSA[78] because of: 1) fluctuations in antibody production and ephemeral nature of C4d deposits; 2) non-complement-dependent effector mechanisms; 3) participation of non-HLA auto- or allo-antibodies[74]; 4) current low incidence (<5%) of traditional “chronic” liver allograft rejection[96]; 5) triggering of non-capillaritis effector mechanisms in target cell populations, such as stellate cells; and 6) paucity of properly preserved specimens to evaluate capillary basement membrane alterations[78]. …”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Potential pathways of injury might not be easily linked to DSA[78] because of: 1) fluctuations in antibody production and ephemeral nature of C4d deposits; 2) non-complement-dependent effector mechanisms; 3) participation of non-HLA auto- or allo-antibodies[74]; 4) current low incidence (<5%) of traditional “chronic” liver allograft rejection[96]; 5) triggering of non-capillaritis effector mechanisms in target cell populations, such as stellate cells; and 6) paucity of properly preserved specimens to evaluate capillary basement membrane alterations[78]. …”
Section: Pathophysiologymentioning
confidence: 99%
“…A variety of other autoantibodies detected in the setting of PCH include cytokeratin 8/18 auto-antibodies[71] and atypical LKM antibodies directed at isoforms of carbonic anhydrase III, subunit β1 of proteasome, and members of different glutathione S-transferase (GST) families[72]. Angiotensin II Type-1 receptor DSA impairs renal allograft outcomes[73], and possibly contributes to fibrosis in combination with HLA DSA in liver allografts[74]. …”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported an increased incidence of occult fibrosis in the presence of posttransplant DSA. [109][110][111][112][113][114][115][116] In pediatric liver transplant, DSA+ versus DSA− patients are more likely to develop advanced fibrosis on protocol biopsy. 110 DSA+ versus DSA− HCV viremic patients had a tripling in their risk of advanced fibrosis by 1 year posttransplant.…”
Section: Donor-specific Alloantibodies In Liver Transplantationmentioning
confidence: 99%
“…A small pediatric liver allograft study demonstrated that patients without DSA had the lowest risk of advanced fibrosis, those with either an HLA or angiotensin II type 1 receptor (AT 1 R) autoantibody had an intermediate risk, and all patients with both HLA DSA and AT 1 R antibodies developed advanced fibrosis. 111 In summary, patients at higher likelihood of developing progressive problems in the face of DSA posttransplant include those with: (1) a higher quantity of HLA DSA (which is difficult to measure with today's technology); (2) IgG3 subclass-positive DSA; (3) those with an additional injury, such as HCV infection, that can upregulate class II expression in the liver and thereby facilitate binding with crosslinking to allow injury to occur 117 ; and (4) possibly those with both HLA and non-HLA antibodies.…”
Section: Donor-specific Alloantibodies In Liver Transplantationmentioning
confidence: 99%
“…Another larger report showed C1q positivity, but more importantly IgG3 subclass positivity, was more strongly associated with adverse outcomes than standard DSA positivity alone . However, it is critical to note that follow‐up liver biopsies were not performed to determine whether fibrosis progression occurred, which is a concern given other group's findings . In addition, the emerging concept of chronic AMR , with more subtle findings that can occur even in patients with normal LFTs, was not part of their histologic evaluation.…”
mentioning
confidence: 99%